Recent Changes in British Wage Inequality: Evidence from Large Firms and Occupations. (19th June 2019) - Schaefer, Daniel; Singleton, Carl
Abstract: Using a linked employer–employee dataset covering large firms, we present new evidence on British wage inequality trends over the past two decades. Differences between firms in the average wages they paid did not drive these trends. Between 1996 and 2005, greater wage variance within firms accounted for 86% of the total increase in wage variance among employees. In the following decade, wage inequality between firms continued to increase, whereas overall wage dispersion decreased. Approximately all the contribution to inequality dynamics from estimated firm‐specific factors, throughout the employee wage distribution, disappears after accounting for the changing occupational content of wages.